2022
DOI: 10.3390/cancers14153739
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Analysis and Identification of Critical RNA-Binding Proteins in Bladder Cancer

Abstract: RBPs in the development and progression of bladder cancer (BC) remains unclear. Here, we elucidated the role of RBPs in predicting the survival of patients with BC. Clinical information and RNA sequencing data of the training and validation cohorts were downloaded from the Cancer Genome Atlas and Gene Expression Omnibus databases, respectively. Survival-related differentially expressed RBPs were identified using Cox regression analyses. A total of 113 upregulated and 54 downregulated RBPs were observed, with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…CD8 + T cells were protective indicators in the process of anti-tumor immunity in various tumors, including BLCA [ 62 , 63 ]. Gu et al found that low-risk BLCA patients exhibited a higher immune infiltration of plasma cells compared to the high-risk group, which was in line with our results [ 64 ]. Interestingly, the Tregs showed an inverse effect in BLCA, though they were associated with decreased survival in many cancers, including breast, melanoma and lung [ 65 , 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…CD8 + T cells were protective indicators in the process of anti-tumor immunity in various tumors, including BLCA [ 62 , 63 ]. Gu et al found that low-risk BLCA patients exhibited a higher immune infiltration of plasma cells compared to the high-risk group, which was in line with our results [ 64 ]. Interestingly, the Tregs showed an inverse effect in BLCA, though they were associated with decreased survival in many cancers, including breast, melanoma and lung [ 65 , 66 ].…”
Section: Discussionsupporting
confidence: 93%
“…Tumors having a greater infiltration of CD8+ T cells, M1 macrophages, and CD20+ cells had a better prognosis than those infiltrated with M0/M2 macrophages and high immunological checkpoint protein expression [ 45 ]. Studies have indicated that low levels of macrophage M0 are strongly related to a better prognosis in bladder cancer patients [ 46 , 47 , 48 ]. Our experimental findings are remarkably congruent with those of the preceding investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, has-miR-20a-3p-regulated Pou2af1 mutations lead to impaired T cells, such as impairment in cytokine production and T follicular helper (Tfh) differentiation [16]. Has-miR-20a-3p-regulated MAP1B upregulation leads to a lower proportion of plasma cells, CD8+ T cells and T cell follicular helper cells, suggesting that MAP1B may be involved in regulating T cell differentiation [17]. It has been reported that asparagine synthetase (Asns), whose expression peaks in effector T cells, may determine the outcome of T cell differentiation, leading to a decrease in the differentiation of TH2 and Treg cells [18].…”
Section: Discussionmentioning
confidence: 99%